Patentes de invención, nuevas tecnologías y la apropiación privada del conocimiento público - Gelles, Jan-David (2005)
In this working paper an examination is made of the logical balance of the deductive argument that commonly appears in various economic texts to justify a system of patents of invention. The examination mentioned should be applied in times of radical technological change in the world to avoid a priori extensions of the legal and institutional protection provided by a system of patents of invention based on past technological realities. The result of the examination shows partial lack of balance when proper account is taken of the financial expenses and coordination efforts by governments as well as of the free distribution of useful knowledge in the fields of biotechnology and the Internet. To refer to that non-legitimate appropriation of public knowledge by the private sector the term ‘epistemo-piracy’ is coined by analogy with ‘bio-piracy’ of common use. The fields of biotechnology and the Internet were chosen because they are preponderant to explain the rise in the number of patents of invention in the world.